CentOS bible - Boronczyk, Tim, 1979- (Wiley Pub., 2009)
"This is one of the first, if not the first comprehensive guide to the CentOS Linux operating system. Linux guru Tim Bornocyzyk, thoroughly covers the topic whether you're a Linux novice or a regular who now wants to master this increasingly popular distribution. First find out how to install and configure CentOS. From there, you'll cover a wealth of Linux and CentOS tools, functions, and techniques, including: how to work in the GNOME and KDE desktop environments; how to use the Linux shell, file system, and text editor; how to configure CUPS printers, Samba for file and printer sharing and other features using GUI tools; and more. For getting the most out of CentOS Linux, this is the book you need to succeed"--Resource description page